Penyakit Myalgia / Nyeri Otot Sebagai Implementasi Pengabdian Masyarakat Berbasis Edukasi Di RW RT 002 / 002 Kelurahan Jayaloka Kecamatan Tebing Tinggi Kabupaten Empat Lawang - Sari, Insan Kurnia; Yanti, Rama; Melania, Karisma; Damayanti, Chera; Situmorang, Ronalen Br.; Rohani, Tuti; Azizah, Danur (Jurnal Kewirausahaan dan Bisnis, 2025)
Myalgia / Muscle pain is a disease with muscle pain conditions caused by excessive muscle tension, causing the muscles to become tense. There are two types of therapy that can be used to treat this muscle pain, namely pharmacological and non-pharmacological therapy. Non-pharmacological therapy is an alternative to medical treatment, such as compressing with water, massaging slowly, not doing excessive physical activity. While pharmacological therapy uses medical treatment aimed at controlling pain using analgesic drugs (Yulis, et al. 2023). The purpose of this Thematic KKN activity is to increase public knowledge about Myalgia / muscle pain through community service activities based on health education for participants who experience Myalgia. The methods used include Counseling about Myalgia / muscle pain using leaflet media and Educating for periodic health checks at the health center. The results of the activity showed that out of 134 people studied, 60 people experienced myagia, both men and women. The number of Myalgia participants was 134 people out of 57 men who were affected by myalgia 18 people and out of 77 women who were affected by myalgia 42 people. So the total who experienced myalgia was 60 people out of 134 people in RW RT 002 / 002 Jayaloka Village, Tebing Tinggi District, Empat Lawang Regency. The results obtained from this activity are that the Counseling activity has been carried out and implemented well, the community already knows about myalgia / muscle pain and however, continuous education is needed by the health center so that the community always remembers what Myalgia is, the signs of myalgia and its symptoms and how to handle it properly. Follow-up plan Holding counseling / education every month at every integrated health post. It is expected that the local government, especially the head of RT.002/RW 002, will invite the community to participate in health check-ups and health posts for adolescents/elderly people carried out by the health center and the Tebing Tinggi health center will be more active in providing education to the community through health cadres about diseases that exist in the community, especially Myalgia